Asymmetric Induction by a Nitrogen (14)N/(15)N Isotopomer in Conjunction with Asymmetric Autocatalysis - Matsumoto, Arimasa (Angew Chem Int Ed Engl, 2016)
Chirality arising from isotope substitution, especially with atoms heavier than the hydrogen isotopes, is usually not considered a source of chirality in a chemical reaction. An N (2) ,N (2) ,N (3) ,N (3)‐tetramethyl‐2,3‐butanediamine containing nitrogen ((14)N/(15)N) isotope chirality was synthesized and it was revealed that this isotopically chiral diamine compound acts as a chiral initiator for asymmetric autocatalysis.